The Influence of the Financial Revolution on the Nature of Firms - Rajan, Raghuram G; Zingales, Luigi (American Economic Review, 2001)
Major technological, regulatory, and institutional changes have made finance more widely available in recent years. The ability of institutions to price a variety of exotic instruments, and to assess and spread risks, has increased. More data on potential borrowers is now available, and it is also more timely. Improvements in accounting disclosure have resulted in greater borrower transparency. Deregulation has resulted in greater competition and better prices in markets. Finally, regulatory barriers protecting the turf of different kinds of institutions have come down, resulting in the emergence of new institutional forms. These changes amount to a bona fide financial revolution. In this article, we focus on the impact the revolution has had on the way firms are (or should be) organized and managed, and on the policy consequences. To do this, we first need to understand what firms are and what drives their organizational structure. A caveat is in order at the outset. Finance is not the only force transforming the nature of firms in the last two decades; deregulation and technological change have also played big roles. These have been explored elsewhere (see e.g., Rajan and Zingales, 2000); hence, our focus. I. Critical Resource Theory